2017
DOI: 10.1002/slct.201701653
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Absorption, Emission and Two‐Photon Absorption Properties of Some Functional 1,3,5‐Triphenylbenzenes

Abstract: International audienceWe report herein the linear optical properties of some extended 1,3,5-triphenylbenzene derivatives 1,3,5-[(1,4-C6H4)CC(4-C6H4X)](3)(C6H3) (3-X; X=NO2, CN, H, OMe, NMe2, NPh2) and briefly discuss the two-photon absorption (2PA) cross-sections determined for the derivatives featuring the most electron-rich substituents, contrasting their 2PA performance with the 2PA values previously gathered for their triphenylisocyanurate analogues N,N',N ''-[(1,4-C6H4)CC(4-C6H4X)](3)(N-3{C(O)}(3)) (1-X).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
6
6
0
Order By: Relevance
“…[c] Calculated at the MPW1PW91/6‐31G* level on computationally‐simpler model complexes (see below) in CH 2 Cl 2 ( f =oscillator strength). [d] 340 [2.50] and 340 [2.50] when calculated at the CAM−B3LYP/6‐31G* level in CH 2 Cl 2 …”
Section: Resultsmentioning
confidence: 99%
“…[c] Calculated at the MPW1PW91/6‐31G* level on computationally‐simpler model complexes (see below) in CH 2 Cl 2 ( f =oscillator strength). [d] 340 [2.50] and 340 [2.50] when calculated at the CAM−B3LYP/6‐31G* level in CH 2 Cl 2 …”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we investigate TPA properties of some octupolar derivatives, namely triphenylisocyanurate, triphenyl-benzene and + (Scheme 1). In previous experimental studies, some of us reported on the linear and NLO properties of substituted triphenyl-isocyanurates, tristyrylisocyanurates and triphenyl-benzene [24][25][26][27][28]. Triazinane-2,4,6-triones, more commonly known as isocyanurates are important cyclotrimeric molecules that attract considerable attention in polymer chemistry in regard to their numerous industrial applications, particularly in the field of foams, elastomers, paints, fibers, and surface coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The two first derivatives i.e. 1-NMe 2 and 2-NMe 2 [24][25][26] exhibit a good NLO activity/transparency trade-off, and, in terms of third-order activity, they were shown to possess high TPA cross-sections. The TPA properties of the studied compounds will be computed using DFT techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently shown that this symmetry can also be potentially beneficial to third-order NLO properties such as two-photon absorption (2PA). Given the very appealing societal prospects for dyes presenting large 2PA cross-sections [5][6][7][8], in particular regarding fluorescence bioimaging when the dye also fluoresces [6,9], we have started exploring the 2PA properties of various families of molecules, such as extended 1,3,5-triaryltriazinane-2,4,6-triones (1-X; Scheme 1) [10,11] or 1,3,5-triphenylbenzene (2-X) [12]. Both 1-X (also known as N,N ,Ntriphenylisocyanurates [13]) and 2-X derivatives proved to be good two-photon absorbers, especially when functionalised by electron-releasing groups at their periphery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the very appealing societal prospects for dyes presenting large 2PA cross-sections [5][6][7][8], in particular regarding fluorescence bioimaging when the dye also fluoresces [6,9], we have started exploring the 2PA properties of various families of molecules, such as extended 1,3,5-triaryltriazinane-2,4,6-triones (1-X; Scheme 1) [10,11] or 1,3,5-triphenylbenzene (2-X) [12]. Both 1-X (also known as N,N ,Ntriphenylisocyanurates [13]) and 2-X derivatives proved to be good two-photon absorbers, especially when functionalised by electron-releasing groups at their periphery [11,12]. Actually, in line with these findings as well as with independent reports [14], we observed that the cross-section of the first 2PA peak for these derivatives increased with the polarisation of the peripheral arms, typically when strongly electron-releasing X substituents were present (X = OMe, NMe 2 , NPh 2 ).…”
Section: Introductionmentioning
confidence: 99%